1998
DOI: 10.1093/ndt/13.suppl_6.43
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of phosphate removal with different dialysis schedules

Abstract: peritoneal fluid makes a reduction of phosphate dietary Phosphate metabolism in chronic renal failure intake impractical, the protein content of the diet being strictly linked to that of phosphate. Even though hypophosphataemia has been reportedWeekly phosphate removal in CAPD has been occasionally in chronic renal failure patients on dialysis reported to be ~70 mmol, with 4×2 l exchanges per treatment [1,2], phosphate (Pi) retention, often associday [12]. This value is quite similar to that found in ated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 4 publications
5
26
1
Order By: Relevance
“…14 The results of our study showed a progressive fall in sP concentration during the first hour of the HD session. Moreover, we found a negative contribution of IPR to TPR in the first 10 min of the HD session which is in accordance with the results of two previous studies.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…14 The results of our study showed a progressive fall in sP concentration during the first hour of the HD session. Moreover, we found a negative contribution of IPR to TPR in the first 10 min of the HD session which is in accordance with the results of two previous studies.…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, we found a negative contribution of IPR to TPR in the first 10 min of the HD session which is in accordance with the results of two previous studies. 7,14 Messa et al 14 showed that during the first 45 min the extracellular phosphate removal was greater than total, which could be explained either by an influx of phosphate into the intracellular space or alternatively by a possible overestimation of the effective distribution volume of phosphate, which during the first 45 min might be lower than that estimated. We chose to investigate alterations in extra-(serum) and intracellular (RBC) inorganic phosphorus concentrations during the first hour of the HD session as detailed data are lacking for this early period of time and it has been shown that this first quadrant of an HD session is critical as more than 30% of the total phosphorus mass removal occurs during it.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thereafter phosphatemia stabilizes until the end of both dialysis procedures. The second flat phase implies attainment of equilibrium between removal of phosphate through the dialyzer and matched release from intracellular pools, just sufficient to replenish blood losses [19]. The finding of sustained and similar phosphate blood levels with two dialysis prescriptions resulting in different hourly phosphate mass removal supports this hypothesis.…”
Section: Discussionmentioning
confidence: 93%
“…Other studies have concentrated on phosphate, which is known to be distributed in at least two to four different compartments [27]. Not surprisingly, a positive impact of longer dialysis was observed for the removal of solutes like β2-microglobulin [2,3,7] and phosphate [1,[8][9][10][11]28]. The different removal when enhancing dialysis Table 2.…”
Section: Discussionmentioning
confidence: 99%